Potential of Ipomoea pes-caprae Extract as an Antibacterial: A Literature Review - Nuralyza, Imasayu; Hanifa, Nisa Isneni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The increasing prevalence of antibiotic resistance shows the urgent need for discovering alternative compounds with potential antibacterial activity. Ipomoea pes-caprae (commonly known as katang-katang) has emerged as a promising natural source of antibacterial agents due to its bioactive constituents, including phenolics, alkaloids, flavonoids, and saponins. The purpose of this article is to review and compare previously reported antibacterial research findings of Ipomoea pes-caprae against various bacterial species. The literature review was conducted using relevant sources obtained from Google Scholar and PubMed databases, covering publications from 2014 to 2024. The findings show that different parts of Ipomoea pes-caprae exhibit antibacterial activity against both Gram-positive and Gram-negative bacterial strains, attributed to the presence of antibacterial compounds. Factors influencing the antibacterial activity of the extracts include the type of test bacteria, the extract concentration, and the solvent used. It can be concluded that Ipomoea pes-caprae has potential as an antibacterial agent.